Pengaruh Perencanaan Pajak Terhadap Nilai Perusahaan Dengan Komisaris Independen Sebagai Variabel Moderasi - Putri, Sintia Bratama; Rachmawati, Nurul Aisyah (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2023)
This study aims to determine the effect of tax planning on firm value with an independent commissioner as a moderating variable. This research is a quantitative study using panel data regression analysis using STATA software. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange in 2020-2022 with a total of 68 samples with the criteria for determining using a purposive sampling technique. Based on the results of the study, it was concluded that the tax planning variable had no significant effect on the firm value variable. The independent commissioner variable cannot moderate the relationship between tax planning and firm value.